IDNLearn.com is the perfect place to get answers, share knowledge, and learn new things. Ask your questions and receive reliable, detailed answers from our dedicated community of experts.
Sagot :
-----------------------------------------------------------
1. x(x+3) = x²+3x
Step by Step:
Apply the Distributive law: (a=x, b=x, c=3)
= xx + x × 3
= xx + 3x
= xx = x²
= x²+3x
-----------------------------------------------------------
2. 3x(4x-7) = 12x²-21x
Step by Step:
Apply the Distributive law: a(b-c) = ab - ac
(a=3x, b=4x, c=7)
= 3x × 4x - 3x × 7
= 3 × 4xx - 3 × 7x
= 12x² - 21x
-----------------------------------------------------------
3. -5x(6x-2) = -30x²+10x
Step by Step:
Apply the Distributive law: a(b-c) = ab - ac
(a = -5x, b = 6x, c = 2)
= -5x × 6x - (-5x) × 2
Apply minus - plus rule: -(-a) = a
= -5x × 6xx + 5 × 2x
= -30x² + 10x
-----------------------------------------------------------
1. x(x+3) = x²+3x
2. 3x(4x-7) = 12x²-21x
3. -5x(6x-2) = -30x² + 10x
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Your questions find answers at IDNLearn.com. Thanks for visiting, and come back for more accurate and reliable solutions.